Correlation between body composition and cardiorespiratory fitness in female adults of different Body Mass Index - Jaafar, Zulkarnain; Ooi, Mun Yooi; Razali, Nurhanani (Edizioni Minerva Medica, 2019)
BACKGROUND: Obesity has become a major public concern as it leads to significant health risk and economic burden especially to the developing countries. The prevalence of obesity is also significantly higher among the female adults. It is also known that low fitness level is a powerful and independent risk factor for premature mortality. However, the understanding of the relationship between overall body composition indices and cardiorespiratory fitness in adults remains limited. This study aimed to investigate the correlation between body composition with cardiorespiratory fitness among normal weight, overweight and obese in female adults. METHODS: Eighty-one female participants aged between 18 to 59 years who cleared the inclusion and exclusion criteria were divided into three groups; normal weight (N.=23), overweight (N.=29) and obese (N.=29). They went through bio-electrical impedance analysis measurement and cardiopulmonary fitness testing using ramp protocol in Sport Medicine human performance lab. RESULTS: It was noted that there was an inverse strong strength significant correlation between VO 2 max and Body Mass Index (r=-0.588, P<0.001, Waist Hip Ratio (r=-0.596, P<0.001), Percentage Body Fat (r=-0.684, P<0.001) and Body Fat Mass (r=-0.667, P<0.001). However, skeletal muscle mass showed no significant correlation with VO 2 max. There was also a high significant difference among the three groups in term of VO 2 max (F=7.683, P=0.001) after alleviating the age factor. CONCLUSIONS: In conclusion, our study showed significant correlation between VO 2 and body composition particularly percentage of body fat (%) and body fat mass (kg). It will be more convenience and cost-effective especially in developing countries, if body composition can be used as an independent entity to predict cardiorespiratory fitness among individual. Furthermore, cardiorespiratory exercise testing showed significant differences of VO 2 max among 3 groups. This will be beneficial if the VO 2 max is used as a tool to predict cardiovascular risk. Therefore, we would suggest in-depth studies to be done in the future to provide more knowledge regarding this important topic on a bigger scale subjects. © 2018 EDIZIONI MINERVA MEDICA.